2001
DOI: 10.1248/bpb.24.1305
|View full text |Cite
|
Sign up to set email alerts
|

Application of the PKCYP-test to Predict the Amount of in Vivo CYP2C11 Using Tolbutamide as a Probe.

Abstract: It is important to be able to predict the drug clearance rate for individual patients in order to select the most appropriate drug dosage regimens. Many attempts have been made to evaluate the drug metabolism capacity of individual patients by using specific probe drugs for cytochrome P450 (CYP) isozymes. 1,2) In addition, several other approaches have been used to predict in vivo drug metabolism, scaling of in vivo metabolic clearance from in vitro data obtained using human liver microsomes or a recombinant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…71 CCl 4 -treated rats have been used as models for low levels of CYP2C11 in the liver. 72 Other examples include Lgals3 73,74 In addition, there were many novel changes in gene expression documented by this study. Many of the observed expression changes for these genes appeared to correlate with the known functional roles of the genes and, in some cases, could be linked with other genes affected by CCl 4 .…”
Section: Discussionmentioning
confidence: 64%
“…71 CCl 4 -treated rats have been used as models for low levels of CYP2C11 in the liver. 72 Other examples include Lgals3 73,74 In addition, there were many novel changes in gene expression documented by this study. Many of the observed expression changes for these genes appeared to correlate with the known functional roles of the genes and, in some cases, could be linked with other genes affected by CCl 4 .…”
Section: Discussionmentioning
confidence: 64%
“…The CYP2C family (2C6 or 2C11) is responsible for the hepatic metabolism of tolbutamide in rats (Azuma et al, 1999;Matsunaga et al, 2001). We found much weaker tolbutamide hydroxylation activity in OM microsomes than in hepatic microsomes; among the tested substrates, tolbutamide was the least metabolized molecule in OM.…”
Section: Downloaded Frommentioning
confidence: 70%
“…We prepared model rats with various degrees of acute hepatic failure induced by administering various doses of CCl 4 . To examine the degree of CL tot decrease in acute hepatic failure, we selected eight probe drugs which are metabolized by various CYP isoforms: caffeine 25) by CYP1A2, doxorubicin 26) by CYP2B1, tolbutamide 27) by CYP2C11, chlorzoxazone 28) by CYP2E1, and cyclosporine A, 29) lidocaine, 30) tacrolimus 29) and zonisamide 31) by CYP3A2. We found that the blood or plasma concentrations of these drugs in CCl 4 -treated rats were significantly higher than those in control rats (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma was separated by centrifugation at 3000ϫg for 10 min and stored at Ϫ30°C. The HPLC assays for caffeine, 17) chlorzoxazone, 18,19) doxorubicin, 20) lidocaine, 21) tolbutamide 22) and zonisamide 23) were carried out according to the cited methods. The blood concentration of cyclosporin A or tacrolimus was measured with a TDx or an IMx analyzer using a commercial assay kit (Tacrolimus II, Dainabot Co., Ltd., Tokyo, Japan), according to the manufacturer's instructions.…”
Section: Materials Adriacin Injectionmentioning
confidence: 99%